Book review of Evaluating literacy instruction: Principles and promising practices. - Shawnee Hardware (Canadian Society for Studies in Education, 2019)
This review provides a description, assessment and critique for Gabriel & Allington's edited book, Evaluating Literacy Instruction: Principles and Promising Practices. As the name suggests, Evaluating Literacy Instruction calls on education practitioners and researchers in the US to design and utilise valid and reliable English Language Arts/Literacy (ELA) evaluation. Additionally, a key theme that is reiterated throughout the book is that education practitioners should design and use evaluations that are culturally and linguistically appropriate for their students. Despite the salience of the information provided, the authors could have used more qualitative data and infographics to improve the readability of the book. The reviewer also recommends that editors include a glossary to help readers understand the technical language associated with literacy evaluation. Overall, the book provides a nuanced understanding of ELA evaluation in the US which will benefit educators and emergent researchers.